2000
DOI: 10.1002/(sici)1099-0968(200005)8:3<225::aid-erv324>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of eating disorder pathology in a cross-ethnic population of female students in South Africa

Abstract: Objective: The purpose of this study was to determine the prevalence of eating disorder pathology in female students representing South Africa's ethnically diverse population. A secondary aim was to explore relationships between eating disorder pathology, Body Mass Index (BMI), and socioeconomic status (SES).Method: In a questionnaire survey of a cross-section of South African college students, the Eating Disorder Inventory (EDI) was administered to a convenience sample of 628 students (52 per cent white, 38.6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
23
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 21 publications
5
23
2
Order By: Relevance
“…The results from our African sample are consistent with earlier research revealing high levels of eating pathology in Black South African women (le Grange, Telch, & Tibbs, 1998;Szabo & Hollands, 1997;Wassenaar, le Grange, Winship, & Lachenicht, 2000). Levels of Bulimia for the African sample in the current study were higher than those reported for a Black African sample in a previous study that also utilized the EDI (Wassenaar et al, 2000).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The results from our African sample are consistent with earlier research revealing high levels of eating pathology in Black South African women (le Grange, Telch, & Tibbs, 1998;Szabo & Hollands, 1997;Wassenaar, le Grange, Winship, & Lachenicht, 2000). Levels of Bulimia for the African sample in the current study were higher than those reported for a Black African sample in a previous study that also utilized the EDI (Wassenaar et al, 2000).…”
Section: Discussionsupporting
confidence: 90%
“…Levels of Bulimia for the African sample in the current study were higher than those reported for a Black African sample in a previous study that also utilized the EDI (Wassenaar et al, 2000). The high levels of bulimia reported in these two groups of African women suggest that cultural aspects of having been raised within Africa itself may be associated with eating pathology.…”
Section: Discussioncontrasting
confidence: 80%
“…Likewise studies have largely reported the preponderance of body-image disorders and eating disorders among females 3,32,35,43 , to the extent that majority of studies reviewed were conducted solely among females. 7,16,19,26,30,33,34 The participants who were students of the College of Technology tend to have disordered eating attitudes compared to those sampled from the University. In Nigeria, there appears to be some discrimination against undergraduates and graduates of College of Technology in favour of their University counterparts 48 , which may impact negatively on the self-esteem of students in College of Technology.…”
Section: Discussionmentioning
confidence: 99%
“…One study conducted in South Africa compared Black and Caucasian samples and reported concerns about body weight and shape among both Black and White populations 18 . Findings from studies such as these have led to an increasing interest in the rates of disordered eating attitudes in the developing world by suggesting an increasing prevalence of disordered eating attitudes and eating disorders [25][26][27] . It has been argued that communities that are considered as "Western" and in which eating disorders are more prevalent tend to influence non-Western societies in various ways including emphasis on thinness 19,28 .…”
Section: Introductionmentioning
confidence: 99%
“…3,4 However, in the changing socio-historical context of post-apartheid South Africa, several surveys of racially diverse groups of adolescents 5,6 and young adults [7][8][9][10] have suggested that non-Caucasian South Africans may in fact not be "immune" to pathological eating disorders. These surveys of ethnically diverse 15-to 25-year-old high school and college students demonstrate that the scores achieved by black girls and women with regard to pathological eating disorders are at least as high as those of Caucasian girls and women.…”
Section: Eating Disorders In Africamentioning
confidence: 99%